2019
DOI: 10.1111/hdi.12747
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, frailty, and mortality among dialysis patients

Abstract: Introduction: Frailty and depression are highly prevalent in the dialysis population, but the association between them, the risk factors for their development, and their independent associations with mortality have not been studied. Methods: We examined 771 patients enrolled in the ACTIVE/ADIPOSE prevalent dialysis cohort study. Fried’s frailty phenotype and the Center for Epidemiologic Studies Depression score were used to determine frailty and presence of depressive symptoms, respectively. We assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 29 publications
4
36
0
4
Order By: Relevance
“…28-30 The prevalence of depression in our study was 53% which is similar to Jaber et al 31 but higher than other studies. 22 There is a growing body of evidence that depression is associated with poor outcomes such as post dialysis fatigue, higher mortality, and hospitalizations. There was a substantial overlap among frailty, cognition, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…28-30 The prevalence of depression in our study was 53% which is similar to Jaber et al 31 but higher than other studies. 22 There is a growing body of evidence that depression is associated with poor outcomes such as post dialysis fatigue, higher mortality, and hospitalizations. There was a substantial overlap among frailty, cognition, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Our study appears to be the first to demonstrate the effect of frailty on adherence to recommendations in hemodialysis patients, also of younger age. Depending on assessment method, several authors reported frailty was three- to tenfold more common in hemodialysis patients compared to older subjects with normal renal function [5,17,22,51,52]. Since low physical activity is a criterion in frailty definition [53], interventions leading to increased physical activity might reduce or reverse frailty status, both directly and indirectly, provided they improve physical fitness or reduce the symptoms of fatigue and exhaustion [54].…”
Section: Discussionmentioning
confidence: 99%
“…At baseline, 13.1% of individuals presented depressive symptoms based on the Center for Epidemiologic Studies Depression scale, 21.8% had frailty, and 10.0% met criteria for both. After 2 years of follow-up, 26.6% of CKD patients had frailty, and 12.7% exhibited depressive symptoms, and depressive symptoms and frailty were independent predictors of mortality (Sy et al, 2019).…”
Section: Depression and Anxiety In Ckdmentioning
confidence: 99%